2019 IEEE/CVF Conference on Computer Vision and Pattern Recognition Workshops (CVPRW) 2019
DOI: 10.1109/cvprw.2019.00318
|View full text |Cite
|
Sign up to set email alerts
|

Adversarial Large-Scale Root Gap Inpainting

Abstract: Root imaging of a growing plant in a non-invasive, affordable, and effective way remains challenging. One approach is to image roots by growing them in a rhizobox, a soil-filled transparent container, imaging them with digital cameras, and segmenting root from soil background. However, due to soil occlusion and the fact that digital imaging is a 2D projection of a 3D object, gaps are present on the segmentation masks, which may hinder the extraction of finely grained root system architecture (RSA) traits. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…7, the CNN would leave gaps when a root was covered by large amounts of soil. An approach such as [84] could be used to recover such gaps which may improve the biological relevance of our root length estimates and potentially facilitate the extraction of more detailed root architecture information.…”
Section: Discussionmentioning
confidence: 99%
“…7, the CNN would leave gaps when a root was covered by large amounts of soil. An approach such as [84] could be used to recover such gaps which may improve the biological relevance of our root length estimates and potentially facilitate the extraction of more detailed root architecture information.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in machine learning applied to image analysis allowed partially overcoming these limitations. For example, deep learning techniques have been used to improve the consistency of classic approaches enhancing the quality of root segmentations [44, 45]. Closest to our work is the recent RootNav 2 [46], which is also based on deep learning models and provides fine-grained metrics distinguishing between MR and LRs.…”
Section: Discussionmentioning
confidence: 99%
“…With accurate RSA segmentations, many existing RSA analysis methods can be used to calculate important root phenotypic traits for analysis. CNN-based RSA segmentation methods also faced the challenge of limited annotated training images, so researchers tried to generate synthetic images for model training [ 125 , 126 ].…”
Section: Cnn-based Analytical Approaches For Image-based Plant Phementioning
confidence: 99%
“…Experimental results showed that measurement accuracies of root phenotypic traits (tip length and number) using corrected segmentations increased 2 to 5 times than those using the raw segmentations. A following study further expanded the model by adding adversarial module at the patch and global levels [ 125 ]. The adversarial module helped the model to learn robust feature representations for root tip inpainting, and the two-level training helped the model to produce accurate results both locally (image patches) and globally (the whole root image).…”
Section: Cnn-based Analytical Approaches For Image-based Plant Phementioning
confidence: 99%